Differences in Menopausal Hormone Therapy Use among Women in Germany between 1998 and 2003 - Scheidt-Nave Christa; Melchert Hans-Ulrich W; Dören Martina; Du Yong; Knopf Hildtraud (BMC, 2007)
Abstract Background To examine the differences in menopausal hormone therapy (MHT) use and user profiles among women in Germany before and after the communication of the Women's Health Initiative (WHI) trial and other study results concerning the risks and benefits of MHT. Methods Current MHT use was ascertained in two periodic German national health surveys conducted in 1997-1999 and 2003-2004. MHT prevalence and user profiles were assessed within each survey. The association of the survey period (2003-2004 vs. 1997-1999) with current MHT use was analyzed in weighted multivariable logistic regression (MLR) models, pooling data from both surveys. Results The overall prevalence of current MHT use decreased by 40.2% from 16.9% of the sample in 1997-1999 to 10.1% in 2003-2004. The difference in prevalence between surveys varied with age decade with the smallest decreases among women 60-69 years of age (20.3% vs. 18.5%), compared to women of younger and older age groups (40-49: 10.7% vs. 3.9%; 50-59: 36.3% vs. 21.3%; 70-79: 5.7% vs. 3.2%). Variables independently associated with higher current MHT use in both health surveys included age category (curvilinear relationship with highest use among women 50-59 years) and residence in West vs. East Germany. A higher social status, lower body mass index, and more health-conscious behaviour were significantly associated with higher current MHT use in the 1997-1999 survey, but these associations were not found in the later survey. MLR analyses confirmed a significant decline in MHT use between the 1997-1999 and 2003-2004 surveys, however, the effect was modified by social status and was not significant among lowest social-status women. Conclusion Current MHT use considerably declined among women in Germany between the pre- and post-WHI era. A convergence of current MHT use among women of higher social status with pre-existing patterns of use among lower social-status women suggests that MHT in Germany is now less likely to be used for health promotion.